The army and democracy : military politics in Pakistan - Shah, Aqil, 1973- (Harvard University Press, 2014)
Since Pakistan gained independence in 1947, only once has an elected government completed its tenure and peacefully transferred power to another elected government. In sharp contrast to neighboring India, the Muslim nation has been ruled by its military for over three decades. Even when they were not directly in control of the government, the armed forces maintained a firm grip on national politics. How the military became Pakistan's foremost power elite and what its unchecked authority means for the future of this nuclear-armed nation are among the crucial questions Aqil Shah takes up in The Army and Democracy. Pakistan's and India's armies inherited their organization, training, and doctrines from their British predecessor, along with an ethic that regarded politics as outside the military domain. But Pakistan's weak national solidarity, exacerbated by a mentality that saw war with India looming around every corner, empowered the military to take national security and ultimately government into its own hands. As the military's habit of disrupting the natural course of politics gained strength over time, it arrested the development of democratic institutions. Based on archival materials, internal military documents, and over 100 interviews with politicians, civil servants, and Pakistani officers, including four service chiefs and three heads of the clandestine Inter-Services Intelligence, The Army and Democracy provides insight into the military's contentious relationship with Pakistan's civilian government. Shah identifies steps for reforming Pakistan's armed forces and reducing its interference in politics, and sees lessons for fragile democracies striving to bring the military under civilian control.--